2018
DOI: 10.1002/elsc.201800087
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nano‐zinc oxide on tropane alkaloid production, h6h gene transcription and antioxidant enzyme activity in Hyoscyamus reticulatus L. hairy roots

Abstract: The use of nanotechnology and biotechnology to improve the production of plant bioactive compounds is growing. Hyoscyamus reticulatus L. is a major source of tropane alkaloids with a wide therapeutic use, including treatment of Parkinson's disease and to calm schizoid patients. In the present study, hairy roots were obtained from two‐week‐old cotyledon explants of H. reticulatus L. using the A7 strain of Agrobacterium rhizogenes. The effects of different concentrations of the signaling molecule nano‐zinc oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…(Table 1). The result was on par with the following findings application of nano particles at low concentrations improves the cell division and elongation in shoot growth (Ali et al, 2019 andAsl et al, 2019).…”
Section: Shoot Length (Cm)supporting
confidence: 72%
“…(Table 1). The result was on par with the following findings application of nano particles at low concentrations improves the cell division and elongation in shoot growth (Ali et al, 2019 andAsl et al, 2019).…”
Section: Shoot Length (Cm)supporting
confidence: 72%
“…In contrast, the supplementation of nanoformulated or nano entrapped micronutrients for the slow or controlled release of nutrients would stimulate the uptake process by plants, promote the growth and productivity of crops, and contribute to maintaining soil health as well [97]. For example, in zinc deficient soil, application of nano zinc oxide at low doses positively influences the growth and physiological responses, such as shoot and root elongation, the fresh dry weight and photosynthesis in many plant species compared to the control [98,99]. Kale et al [77] also showed that application of zinc oxide nanoparticles with other fertilizer in zinc deficient soil, not only promotes nutrient use efficiency but also increases barley productivity by 91% compared to the control, whereas traditional bulk ZnSO 4 increases productivity by 31% compared to the control.…”
Section: Nanofertilizers: An Efficient Source Of Balanced Crop Nutmentioning
confidence: 99%
“…Iron oxide nanoparticles (FeNPs) cause tropane alkaloids hyoscyamine and scopolamine accumulation in HRCs of Hyoscyamus reticulates [70]. The H. reticulatus hairy roots treated with ZnO induced the highest levels of hyoscyamine and scopolamine [71].…”
Section: Temperature Variationmentioning
confidence: 99%